Reconstructing Indo-European Metaphors and Metonymies: a Cognitive Linguistic Approach to Comparative Poetics - Ginevra, Riccardo (Annali del Dipartimento di Studi Letterari, Linguistici e Comparati. Sezione linguistica, 2021)
This contribution aims to show how uniting Comparative Indo-European (IE) Poetics and Cognitive Linguistics is valuable to both disciplines. It first reconstructs, through the methodology of Comparative Poetics, a coherent IE -figurative system underlying the widespread expressions of the type to be alive is to be in the light and the connected figurative usage of to see for to live. Next, it analyzes this IE system through Conceptual Metaphor Theory and other cognitive linguistic frameworks, arguing that it results from both metaphoric processes (“Event Structure Conceptual Metaphor”) and metonymic ones (subevent for event metonymy).